Dementia Frequently Coexists With Hepatic Encephalopathy but Not Other Cirrhosis Complications in US Veterans. (17th March 2023) - Adejumo, Adeyinka; Noll, Alan; Rogal, Shari S.; Yakovchenko, Vera; Chia, Linda; Spoutz, Patrick; Morgan, Timothy R.; Bajaj, Jasmohan S.
Abstract : INTRODUCTION: Hepatic encephalopathy (HE) is a common decompensating event in patients with cirrhosis. Because of the aging population of patients with cirrhosis, differentiating HE from nonhepatic etiologies of cognitive impairment, such as dementia, is increasingly important. METHODS: Veterans with cirrhosis were identified via International Classification of Diseases -10 codes between October 1, 2019, and September 30, 2021, using the VA Corporate Data Warehouse. Baseline characteristics were compared between cohorts based on the presence vs absence of dementia. Factors associated with having a diagnosis of dementia were evaluated using multivariate logistic regression models, adjusting for demographics, comorbid illnesses, cirrhosis etiology, and cirrhosis complications. RESULTS: A total of 71, 552 veterans with cirrhosis were identified, of which, 5, 647 (7.89%) veterans had a diagnosis of dementia. Veterans with dementia were older, more frequently White, urban located, and diagnosed with alcohol-related cirrhosis, metabolic syndrome, brain trauma, and cerebrovascular disease more frequently. On multivariable analysis, the presence of any decompensating event was associated with dementia. Multivariable analysis of individual decompensating events revealed HE to be associated with a dementia diagnosis, but not ascites, independent of other risk factors analyzed. DISCUSSION: Dementia is commonly diagnosed in patients with cirrhosis and correlates with a diagnosis of HE, independent of alcohol use, brain injury, age, and other metabolic risk factors. Dementia did not correlate with other decompensating events. Increased awareness of the overlap between dementia and HE, as well as reliable diagnostic and treatment strategies, is needed for the aging population of veterans with cirrhosis.